(untitled) (Research, Society and Development, 2021)
This study aimed to apply cellulose acetate (CA) films incorporated with oregano essential oil (OEO) to inhibit bacteria growth associated with spoilage of meat products (Weissella viridescens (microaerophilic) and Pseudomonas fluorescens (aerobic)) and evaluate its effect on the shelf life of vacuum-packed sliced ham (VPSH). CA films were produced using acetone solvent, adding 25, 35, 50, or 75 mg of OEO per film. Antimicrobial activity and mechanical properties of films were determined. CA films in Petri dishes showed a better antimicrobial effect against W. viridescens than P. fluorescens. As VPSH, presents a microaerophilic environment, product shelf life was determined fitting Baranyi and Roberts’ model to W. viridescens’ growth experimental data, at 8 °C. OEO did not modify films’ mechanical properties. Application of the CA film with 75 mg of OEO decreased value of W. viridescens, increased its value, resulting in a ham` shelf-life increased by eight days, demonstrating excellent application potential.